The emperor's caretaker. 3 - Hiiragi, Ichiha; Shoutoto, Aya (Square-Enix Manga & Books, 2025)
Dark clouds loom over the once-peaceful inner palace after the attack on Imperial regent Souren, compelling the young Emperor Zhiyou to take action as only he can. Emperor's caretaker Linhua observes her charge with growing concern, while Souren and his watchful eye are never far as well. With Souren virtually everywhere Linhua goes, it's only a matter of time before the two find themselves closer than ever before...